Exercise of reflection on the aesthetic category Ugly in its opposition to the Beautiful (an attempt) - Falleiros, Flavia Nascimento [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2017)
This paper attempts to examine the aesthetic category of the Ugly, in its opposition to the Beautiful. It begins with a synthetic exposition of the main elements of the definition of classical beauty, established since the ancient Greeks, validated during the Renaissance and which has been questioned most clearly since the eighteenth century. In order to illustrate the growing rupture with the classical pattern of beauty, this exposition is followed by the analysis of some passages from Diderot's Essais sur la peinture, and Rimbaud's poem Venus Anadyomene, which are significant texts to show and understand how the Ugly gradually took place and became an aesthetic category fully valid in artistic practices.
Keywords: Aesthetics; Diderot; Rimbaud; Ugly and Beauty